Martensitic stainless steel material

By adjusting the chemical composition and specific inclusion distribution of Martensite stainless steel, the corrosion resistance in SOx and NOx environments is improved, and the problem of insufficient corrosion resistance in the prior art is solved, and high strength and excellent corrosion resistance are achieved sex.

CN119213156APending Publication Date: 2024-12-27NIPPON STEEL CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038441.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-25
Filing Date
2023-05-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing Martensite stainless steel material has insufficient corrosion resistance in the corrosion environment mixed with SOx and NOx, and cannot effectively resist corrosion caused by the acidic environment.

Method used

By adjusting the chemical composition, increasing the ratio of Mg oxides to replace Ca oxides, more Mg oxides are formed to improve corrosion resistance, and controlling the distribution of specific inclusions in the steel to stabilize the ratio and satisfying the specific element content Range and ratio requirements.

Benefits of technology

It realizes a Martensite stainless steel with high strength and excellent corrosion resistance in a corrosion environment mixed with SOx and NOx, ensuring the yield strength and corrosion resistance of the steel, and is suitable for environments with high requirements in CO2 storage technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118371190000331
    Figure BDA0005118371190000331
  • Figure BDA0005118371190000341
    Figure BDA0005118371190000341
  • Figure BDA0005118371190000351
    Figure BDA0005118371190000351
Patent Text Reader

Abstract

Provided is a martensitic stainless steel material having high strength and excellent corrosion resistance in a corrosive environment in which SOx and NOx are mixed. This martensitic stainless steel material satisfies the chemical composition described in the description and satisfies formula (1). And the yield strength is 862 MPa or more. In the martensitic stainless steel material, the ratio of the number of Mg oxides having an equivalent circle diameter of 2.0 [mu] m or more with respect to the number of Ca oxides having an equivalent circle diameter of 2.0 [mu] m or more, Ca sulfides having an equivalent circle diameter of 2.0 [mu] m or more, and Mg oxides having an equivalent circle diameter of 2.0 [mu] m or more is 45.0% or more, 0.0010 < = Ca + Mg < = 0.0050 (1). The content of the corresponding element is substituted in mass% at the element symbol in formula (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a steel material, and more particularly to a martensitic stainless steel material. Background Art

[0002] Currently, the increase in the concentration of carbon dioxide (CO2) on the ground has become a global problem. Therefore, measures to suppress CO2 emissions are being promoted. Among such measures to suppress CO2 emissions, CCUS has received particular attention.

[0003] CCUS is the abbreviation of Carbon Dioxide Capture, Utilization and Storage. In other words, CCUS includes three technologies: CO2 recovery, utilization and storage. Among them, as a technology for storing CO2, the technology that recovers CO2 emitted from industrial facilities such as power plants and factories and compresses and stores CO2 in depleted oil wells has attracted much attention.

[0004] Steel materials used in such CO2 storage technology require high strength in order to pressurize CO2 into depleted oil wells. In addition, CO2 is a corrosive substance that corrodes steel materials. Therefore, steel materials used in CO2 storage technology are required to have excellent corrosion resistance in a corrosive environment containing a large amount of CO2.

[0005] Until now, as steel materials having high strength and excellent corrosion resistance in corrosive environments, martensitic stainless steel materials containing about 13 mass % of Cr, represented by APIL80 13Cr steel materials and super 13Cr steel materials with reduced C content, have been known. Specifically, Japanese Patent Application Laid-Open No. 2000-192196 (Patent Document 1) and Japanese Patent Application Laid-Open No. 2012-136742 (Patent Document 2) propose martensitic stainless steel materials having high strength and excellent corrosion resistance in corrosive environments.

[0006] The martensitic stainless steel material proposed in Patent Document 1 is a martensitic stainless steel material for oil wells, which contains, by weight%, C: 0.001-0.05%, Si: 0.05-1%, Mn: 0.05-2%, P: 0.025% or less, S: 0.01% or less, Cr: 9-14%, Mo: 3.1-7%, Ni: 1-8%, Co: 0.5-7%, sol.Al: 0.001-0.1%, N: 0.05% or less, O (oxygen): 0.01% or less, Cu: 0-5%, W: 0-5%, and the balance is Fe and impurities. When Mo is contained, the Ms point decreases. Therefore, the steel material contains Mo and Co, thereby suppressing the decrease of the Ms point and making the microstructure a martensitic single-phase structure. Patent Document 1 discloses the following: As a result, the steel material can improve the corrosion resistance in a corrosive environment while maintaining a yield strength of 551 MPa or more.

[0007] The martensitic stainless steel material proposed in Patent Document 2 is a martensitic stainless steel seamless steel pipe, which contains C: 0.01% or less, Si: 0.5% or less, Mn: 0.1-2.0%, P: 0.03% or less, S: 0.005% or less, Cr: 14.0-15.5%, Ni: 5.5-7.0%, Mo: 2.0-3.5%, Cu: 0.3-3.5%, V: 0.20% or less, Al: 0.05% or less, N: 0.06% or less, and the balance is Fe and impurities. The yield strength of the steel is 655-862MPa, and the yield ratio is 0.90 or more. For the steel, Patent Document 2 discloses that by making the C content less than 0.01%, adjusting Cr, Ni and Mo to an appropriate range, and containing an appropriate amount of Cu and V or an appropriate amount of W, excellent corrosion resistance in a corrosive environment can be obtained.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2000-192196

[0011] Patent Document 2: Japanese Patent Application Publication No. 2012-136742 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] As mentioned above, in the storage technology of carbon dioxide (CO2), the recovered CO2 is compressed and stored in depleted oil wells, etc. On the other hand, CO2 recovered from industrial facilities such as power plants and factories is sometimes mixed with oxides such as SOx and NOx. SOx is a general term for sulfur oxides represented by SO2. NOx is a general term for nitrogen oxides represented by NO2. SOx and NOx dissolve in water to form acidic compounds (sulfuric acid, nitric acid, etc.). That is, when SOx and NOx are mixed with CO2, the corrosive environment tends to be acidic, and the steel in the corrosive environment is easily further corroded. Therefore, for the steel used in such a storage technology of carbon dioxide, not only high strength is required, but also excellent corrosion resistance in a corrosive environment mixed with SOx and NOx is required.

[0014] Patent Documents 1 and 2 above propose martensitic stainless steel materials having high strength and excellent corrosion resistance in a corrosive environment. However, Patent Documents 1 and 2 above do not conduct any research on the corrosion resistance of steel materials in a corrosive environment mixed with SOx and NOx.

[0015] An object of the present disclosure is to provide a martensitic stainless steel material having high strength and excellent corrosion resistance in a corrosive environment containing SOx and NOx.

[0016] Solutions for solving problems

[0017] The present invention discloses a martensitic stainless steel material, which is

[0018] C: 0.030% or less,

[0019] Si: 1.00% or less,

[0020] Mn: 1.00% or less,

[0021] P: 0.030% or less,

[0022] S: 0.0050% or less,

[0023] Cr: 11.00~14.00%,

[0024] Ni: 4.00~7.50%,

[0025] Mo: 1.50-4.50%,

[0026] Co: 0.01-0.50%,

[0027] Ti: 0.05-0.30%,

[0028] V: 0.01~1.00%,

[0029] Ca: 0.0005~0.0050%,

[0030] Mg: 0.0005~0.0050%,

[0031] Al: 0.001~0.100%,

[0032] N: 0.0500% or less,

[0033] O: 0.0500% or less,

[0034] Cu: 0-3.50%,

[0035] Nb: 0-0.50%,

[0036] Zr: 0~0.050%,

[0037] W: 0~2.00%,

[0038] B: 0~0.0050%,

[0039] Rare earth elements: 0 to 0.0050%, and

[0040] Balance: Fe and impurities,

[0041] Within the content range of the element of the martensitic stainless steel material, the content of the element satisfies the formula (1),

[0042] The yield strength of the martensitic stainless steel is 862 MPa or more.

[0043] In the martensitic stainless steel,

[0044] The number ratio of Mg oxides having a circle equivalent diameter of 2.0 μm or more to Ca oxides having a circle equivalent diameter of 2.0 μm or more, Ca sulfides having a circle equivalent diameter of 2.0 μm or more, and Mg oxides having a circle equivalent diameter of 2.0 μm or more is 45.0% or more,

[0045] 0.0010≤Ca+Mg≤0.0050 (1)

[0046] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (1).

[0047] Effects of the Invention

[0048] The martensitic stainless steel material disclosed in the present invention has high strength and excellent corrosion resistance in a corrosive environment in which SOx and NOx are mixed. DETAILED DESCRIPTION

[0049] First, the inventors studied a martensitic stainless steel material having high strength and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx from the viewpoint of chemical composition. As a result, the inventors believed that if the martensitic stainless steel material is as follows, it is possible to take into account both a yield strength of 862MPa (125ksi) or more and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx: C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.030% or less, S: 0.0050% or less, Cr: 11.00-14.00%, Ni: 4.00-7.50%, Mo: 1.50-4.50%, Co: 0.0 ... .01~0.50%, Ti: 0.05~0.30%, V: 0.01~1.00%, Ca: 0.0005~0.0050%, Mg: 0.0005~0.0050%, Al: 0.001~0.100%, N: less than 0.0500%, O: less than 0.0500%, Cu: 0~3.50%, Nb: 0~0.50%, Zr: 0~0.050%, W: 0~2.00%, B: 0~0.0050%, rare earth elements: 0~0.0050%, and the balance: Fe and impurities.

[0050] Here, in a martensitic stainless steel material having the above chemical composition and a yield strength of more than 862MPa, oxygen (O) in the steel is sometimes fixed as Ca oxide using Ca, and there is a situation where the amount of O solid solution in the steel is reduced. In this case, Ca oxide is formed in the steel. On the other hand, the inventors of the present invention conducted a detailed study and found that in a corrosive environment mixed with SOx and NOx, coarse Ca oxides are likely to become the starting point of pitting corrosion. Here, as mentioned above, in the case of SOx and NOx being mixed, the corrosive environment tends to be acidic, and the pH in the environment is reduced. On the other hand, Ca oxides are easily dissolved in an acidic environment. Therefore, in a corrosive environment where SOx and Nox are mixed and the pH is reduced, coarse Ca oxides are likely to dissolve and become the starting point of pitting corrosion. That is, it is clear from the research of the inventors of the present invention that when a large number of coarse Ca oxides are formed in the steel, it is possible that excellent corrosion resistance cannot be obtained in a corrosive environment mixed with SOx and NOx.

[0051] Therefore, the inventors of the present invention thought of using Mg to fix O as Mg oxide instead of Ca, thereby improving the corrosion resistance of steel. Compared with Ca oxide, Mg oxide is not easily dissolved even in an acidic environment. Therefore, if Mg oxide is formed in steel instead of Ca oxide, it is possible to improve the corrosion resistance of steel in a corrosive environment mixed with SOx and NOx.

[0052] Here, in this specification, Ca oxides having an equivalent circle diameter of 2.0 μm or more are also referred to as "coarse Ca oxides". In this specification, Ca sulfides having an equivalent circle diameter of 2.0 μm or more are also referred to as "coarse Ca sulfides". In this specification, Mg oxides having an equivalent circle diameter of 2.0 μm or more are also referred to as "coarse Mg oxides". In this specification, coarse Ca oxides, coarse Ca sulfides, and coarse Mg oxides are also collectively referred to as "specific inclusions". Specific inclusions are inclusions obtained by fixing O or S as oxides or sulfides using Ca or Mg in the martensitic stainless steel material having the above-mentioned chemical composition.

[0053] As a result of detailed studies by the present inventors, it was found that if the ratio of the number of coarse Mg oxides to the number of coarse Ca oxides, coarse Ca sulfides and coarse Mg oxides is 45.0% or more, the martensitic stainless steel material having the above chemical composition can achieve both a yield strength of 862 MPa or more and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx. That is, in the martensitic stainless steel material of the present embodiment, the chemical composition is such that the ratio of the number of coarse Mg oxides to the number of specific inclusions is 45.0% or more. As a result, the martensitic stainless steel material of the present embodiment has a yield strength of 862 MPa or more and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx.

[0054] As a result of further detailed studies by the present inventors based on the above findings, it was found that the ratio of the number of coarse Mg oxides to the number of specific inclusions can be stably increased to 45.0% or more by having not only the above chemical composition but also a chemical composition satisfying the following formula (1).

[0055] 0.0010≤Ca+Mg≤0.0050 (1)

[0056] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (1).

[0057] It is defined as Fn1 = Ca + Mg. Fn1 is an index related to Ca oxide and Mg oxide. If Fn1 is too low, Ca and Mg cannot fully fix O as oxide, and a part of O remains in the steel in a solid solution state. On the other hand, if Fn1 is too high, Mg oxide is modified by Ca, and there is a situation where the ratio of the number of coarse Mg oxides to the number of specific inclusions decreases. Therefore, in this embodiment, Fn1 is set to 0.0010 to 0.0050 on the premise of having the above-mentioned chemical composition.

[0058] As described above, the martensitic stainless steel material of the present embodiment has the above-mentioned chemical composition and satisfies the formula (1), has a yield strength of 862 MPa or more, and makes the ratio of the number of coarse Mg oxides to the number of specific inclusions 45.0% or more. As a result, the martensitic stainless steel material of the present embodiment has high strength and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx.

[0059] The gist of the martensitic stainless steel material of the present embodiment completed based on the above findings is as follows.

[0060] [1] A martensitic stainless steel material, which, in terms of mass %,

[0061] C: 0.030% or less,

[0062] Si: 1.00% or less,

[0063] Mn: 1.00% or less,

[0064] P: 0.030% or less,

[0065] S: 0.0050% or less,

[0066] Cr: 11.00~14.00%,

[0067] Ni: 4.00~7.50%,

[0068] Mo: 1.50-4.50%,

[0069] Co: 0.01-0.50%,

[0070] Ti: 0.05-0.30%,

[0071] V: 0.01~1.00%,

[0072] Ca: 0.0005~0.0050%,

[0073] Mg: 0.0005~0.0050%,

[0074] Al: 0.001~0.100%,

[0075] N: 0.0500% or less,

[0076] O: 0.0500% or less,

[0077] Cu: 0-3.50%,

[0078] Nb: 0-0.50%,

[0079] Zr: 0~0.050%,

[0080] W: 0~2.00%,

[0081] B: 0~0.0050%,

[0082] Rare earth elements: 0 to 0.0050%, and

[0083] Balance: Fe and impurities,

[0084] Within the content range of the element of the martensitic stainless steel material, the content of the element satisfies the formula (1),

[0085] The yield strength of the martensitic stainless steel is 862 MPa or more.

[0086] In the martensitic stainless steel,

[0087] The number ratio of Mg oxides having a circle equivalent diameter of 2.0 μm or more to Ca oxides having a circle equivalent diameter of 2.0 μm or more, Ca sulfides having a circle equivalent diameter of 2.0 μm or more, and Mg oxides having a circle equivalent diameter of 2.0 μm or more is 45.0% or more,

[0088] 0.0010≤Ca+Mg≤0.0050 (1)

[0089] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (1).

[0090] [2] The martensitic stainless steel material according to [1], wherein

[0091] It contains a selection of

[0092] Cu: 0.01~3.50%,

[0093] Nb: 0.01-0.50%,

[0094] Zr: 0.001~0.050%,

[0095] W: 0.01~2.00%,

[0096] B: 0.0001~0.0050%, and

[0097] Rare earth elements: one or more elements selected from the group consisting of 0.0001 to 0.0050%.

[0098] [3] The martensitic stainless steel material according to [1] or [2], wherein

[0099] Within the content range of the element of the martensitic stainless steel material, the content of the element satisfies the formula (2),

[0100] In the martensitic stainless steel,

[0101] The total number density of the Ca oxide with a circle equivalent diameter of 2.0 μm or more, the Ca sulfide with a circle equivalent diameter of 2.0 μm or more, and the Mg oxide with a circle equivalent diameter of 2.0 μm or more is 1000 / cm 2 above,

[0102] Ca / S≥0.80 (2)

[0103] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (2).

[0104] The shape of the martensitic stainless steel material of the present embodiment is not particularly limited. The martensitic stainless steel material of the present embodiment can be a steel pipe, round steel (solid material), or steel plate. In addition, round steel refers to a bar steel having a circular cross section perpendicular to the axial direction. In addition, the steel pipe can be a seamless steel pipe or a welded steel pipe.

[0105] Hereinafter, the martensitic stainless steel material of the present embodiment will be described in detail. Unless otherwise specified, "%" for an element represents mass %. In the following description, the martensitic stainless steel material is also simply referred to as "steel material".

[0106] [Chemical composition]

[0107] The martensitic stainless steel material according to the present embodiment contains the following elements.

[0108] C: 0.030% or less

[0109] It is inevitable to contain carbon (C). That is, the lower limit of the C content exceeds 0%. C improves the hardenability of the steel, thereby improving the strength of the steel. On the other hand, if the C content is too high, even if the content of other elements is within the scope of the present embodiment, the strength of the steel will become too high. As a result, the corrosion resistance of the steel will decrease. Therefore, the C content is less than 0.030%. The preferred upper limit of the C content is 0.028%, more preferably 0.025%, further preferably 0.020%, and further preferably 0.018%. The C content is preferably as low as possible. However, an extreme reduction in the C content will increase manufacturing costs. Therefore, considering industrial production, the preferred lower limit of the C content is 0.001%, more preferably 0.003%, and further preferably 0.005%.

[0110] Si: 1.00% or less

[0111] Silicon (Si) is inevitably contained. That is, the lower limit of the Si content exceeds 0%. Si deoxidizes the steel. On the other hand, if the Si content is too high, the hot workability of the steel will decrease even if the content of other elements is within the range of the present embodiment. Therefore, the Si content is 1.00% or less. In order to effectively obtain the above-mentioned effect, the preferred lower limit of the Si content is 0.01%, more preferably 0.05%, further preferably 0.10%, and further preferably 0.15%. The preferred upper limit of the Si content is 0.80%, more preferably 0.70%, further preferably 0.60%, further preferably 0.50%, and further preferably 0.45%.

[0112] Mn: 1.00% or less

[0113] Manganese (Mn) is inevitably contained. That is, the lower limit of Mn content exceeds 0%. Mn improves the hardenability of steel, thereby improving the strength of steel. On the other hand, if Mn content is too high, even if other element contents are within the scope of the present embodiment, the corrosion resistance of steel will also decrease. Therefore, Mn content is below 1.00%. In order to effectively obtain the above-mentioned effect, the preferred lower limit of Mn content is 0.01%, more preferably 0.05%, further preferably 0.10%, further preferably 0.15%. The preferred upper limit of Mn content is 0.90%, more preferably 0.80%, further preferably 0.70%, further preferably 0.60%.

[0114] P: 0.030% or less

[0115] Phosphorus (P) is an impurity that is inevitably contained. That is, the lower limit of the P content exceeds 0%. If the P content is too high, even if the content of other elements is within the range of the present embodiment, P will segregate at the grain boundaries, and the corrosion resistance of the steel will decrease. Therefore, the P content is less than 0.030%. The preferred upper limit of the P content is 0.025%, more preferably 0.020%, and further preferably 0.018%. The P content is preferably as low as possible. However, an extreme reduction in the P content will increase manufacturing costs. Therefore, considering industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.002%, and further preferably 0.003%.

[0116] S: 0.0050% or less

[0117] Sulfur (S) is an impurity that is inevitably contained. That is, the lower limit of the S content exceeds 0%. If the S content is too high, even if the content of other elements is within the range of the present embodiment, S will segregate at the grain boundaries, and the hot workability of the steel will decrease. Therefore, the S content is 0.0050% or less. The preferred upper limit of the S content is 0.0040%, more preferably 0.0030%, further preferably 0.0025%, and further preferably 0.0020%. The S content is preferably as low as possible. However, an extreme reduction in the S content will increase the manufacturing cost. Therefore, considering industrial production, the preferred lower limit of the S content is 0.0001%, more preferably 0.0003%, and further preferably 0.0005%.

[0118] Cr: 11.00~14.00%

[0119] Chromium (Cr) forms a passivation film on the surface of the steel material, thereby improving the corrosion resistance of the steel material. If the Cr content is too low, even if the contents of other elements are within the range of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Cr content is too high, even if the contents of other elements are within the range of the present embodiment, ferrite will be contained in the structure, which sometimes makes it difficult to ensure sufficient strength. Therefore, the Cr content is 11.00 to 14.00%. The preferred lower limit of the Cr content is 11.20%, more preferably 11.40%, further preferably 11.60%, further preferably 11.80%, and further preferably 12.00%. The preferred upper limit of the Cr content is 13.80%, more preferably 13.60%, and further preferably 13.50%.

[0120] Ni: 4.00~7.50%

[0121] Nickel (Ni) improves the hardenability of steel, thereby improving the yield strength of steel. Ni also improves the hot workability of steel. If the Ni content is too low, even if the content of other elements is within the scope of the present embodiment, the above-mentioned effect cannot be fully obtained. On the other hand, if the Ni content is too high, even if the content of other elements is within the scope of the present embodiment, the corrosion resistance of the steel is sometimes reduced. Thus, the Ni content is 4.00 to 7.50%. The preferred lower limit of the Ni content is 4.20%, more preferably 4.50%, more preferably 5.00%, more preferably 5.20%, more preferably 5.30%, and more preferably 5.50%. The preferred upper limit of the Ni content is 7.40%, more preferably 7.20%, more preferably 7.00%, and more preferably 6.50%.

[0122] Mo: 1.50~4.50%

[0123] Molybdenum (Mo) stabilizes the passivation film and improves the corrosion resistance of the steel. If the Mo content is too low, even if the contents of other elements are within the scope of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Mo content is too high, even if the contents of other elements are within the scope of the present embodiment, it is difficult to stabilize the austenite. As a result, there is a situation where the microstructure after tempering contains more ferrite, and the corrosion resistance of the steel is reduced. Therefore, the Mo content is 1.50 to 4.50%. The preferred lower limit of the Mo content is 1.80%, more preferably 2.00%, and further preferably 2.30%. The preferred upper limit of the Mo content is 4.30%, more preferably 4.00%, and further preferably 3.80%.

[0124] Co: 0.01~0.50%

[0125] Cobalt (Co) stabilizes the passivation film and improves the corrosion resistance of the steel. Co also improves the hardenability of the steel, thereby increasing the yield strength of the steel. If the Co content is too low, even if the contents of other elements are within the scope of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Co content is too high, even if the contents of other elements are within the scope of the present embodiment, the toughness of the steel will decrease. Therefore, the Co content is 0.01 to 0.50%. The preferred lower limit of the Co content is 0.02%, more preferably 0.03%, and further preferably 0.05%. The preferred upper limit of the Co content is 0.45%, more preferably 0.40%, and further preferably 0.35%.

[0126] Ti: 0.05~0.30%

[0127] Titanium (Ti) combines with C and / or N to form carbides or nitrides. As a result, the yield strength of the steel is improved. If the Ti content is too low, even if the contents of other elements are within the scope of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Ti content is too high, even if the contents of other elements are within the scope of the present embodiment, the strength of the steel will become too high and the corrosion resistance of the steel will decrease. Therefore, the Ti content is 0.05 to 0.30%. The preferred lower limit of the Ti content is 0.06%, more preferably 0.08%. The preferred upper limit of the Ti content is 0.25%, more preferably 0.20%, and further preferably 0.18%.

[0128] V: 0.01~1.00%

[0129] Vanadium (V) improves the hardenability of steel, thereby improving the yield strength of steel. If the V content is too low, even if the contents of other elements are within the scope of the present embodiment, the above-mentioned effect cannot be fully obtained. On the other hand, if the V content is too high, even if the contents of other elements are within the scope of the present embodiment, the strength of the steel will become too high, and the corrosion resistance of the steel will also decrease. Therefore, the V content is 0.01 to 1.00%. The preferred lower limit of the V content is 0.02%, more preferably 0.04%. The preferred upper limit of the V content is 0.80%, more preferably 0.60%.

[0130] Ca: 0.0005~0.0050%

[0131] Calcium (Ca) improves the hot workability of steel by fixing S in steel as sulfide and rendering it harmless. If the Ca content is too low, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Ca content is too high, coarse Ca oxides will be formed in the steel, and the corrosion resistance of the steel will decrease, even if the contents of other elements are within the range of the present embodiment. Therefore, the Ca content is 0.0005 to 0.0050%. The preferred lower limit of the Ca content is 0.0006%, more preferably 0.0008%, and further preferably 0.0010%. The preferred upper limit of the Ca content is 0.0045%, more preferably 0.0040%, further preferably 0.0035%, further preferably 0.0030%, and further preferably 0.0025%.

[0132] Mg: 0.0005~0.0050%

[0133] Magnesium (Mg) improves the corrosion resistance of steel by fixing O in the steel as oxides to make it harmless. If the Mg content is too low, even if the contents of other elements are within the scope of the present embodiment, the above-mentioned effects cannot be fully obtained. On the other hand, if the Mg content is too high, even if the contents of other elements are within the scope of the present embodiment, coarse Mg oxides will be formed in the steel, and the corrosion resistance of the steel will decrease. Therefore, the Mg content is 0.0005-0.0050%. The preferred lower limit of the Mg content is 0.0006%, more preferably 0.0007%, and further preferably 0.0008%. The preferred upper limit of the Mg content is 0.0045%, more preferably 0.0040%, and further preferably 0.0035%.

[0134] Al: 0.001~0.100%

[0135] Aluminum (Al) deoxidizes steel. If the Al content is too low, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment. On the other hand, if the Al content is too high, coarse oxides will be generated even if the contents of other elements are within the range of the present embodiment, and the corrosion resistance of the steel will decrease. Therefore, the Al content is 0.001 to 0.100%. The preferred lower limit of the Al content is 0.005%, more preferably 0.010%, and further preferably 0.015%. The preferred upper limit of the Al content is 0.080%, more preferably 0.060%, further preferably 0.055%, further preferably 0.050%, and further preferably 0.040%. The Al content referred to in this specification refers to the content of sol.Al (acid-soluble Al).

[0136] N: 0.0500% or less

[0137] It is inevitable to contain nitrogen (N). That is, the lower limit of the N content exceeds 0%. N combines with Ti to form fine Ti nitrides. As a result, the yield strength of the steel is improved. On the other hand, if the N content is too high, even if the content of other elements is within the range of the present embodiment, coarse nitrides will be formed, and the corrosion resistance of the steel will decrease. Therefore, the N content is less than 0.0500%. The preferred upper limit of the N content is 0.0450%, more preferably 0.0400%, further preferably 0.0350%, and further preferably 0.0300%. In order to more effectively obtain the above-mentioned effect, the preferred lower limit of the N content is 0.0015%, more preferably 0.0020%, further preferably 0.0030%, and further preferably 0.0040%.

[0138] O: 0.0500% or less

[0139] Oxygen (O) is an impurity that is inevitably contained. That is, the lower limit of the O content exceeds 0%. O forms oxides and reduces the corrosion resistance of the steel. Therefore, if the O content is too high, even if the contents of other elements are within the scope of the present embodiment, the corrosion resistance of the steel will be significantly reduced. Therefore, the O content is less than 0.0500%. The preferred upper limit of the O content is 0.0400%, more preferably 0.0300%, and further preferably 0.0200%. The O content is preferably as low as possible. However, an extreme reduction in the O content will increase the manufacturing cost. Therefore, considering industrial production, the preferred lower limit of the O content is 0.0005%, more preferably 0.0010%, and further preferably 0.0015%.

[0140] The balance of the martensitic stainless steel material of the present embodiment is Fe and impurities. Here, impurities refer to substances mixed from ores and scraps as raw materials or from the manufacturing environment when industrially manufacturing steel materials, and are not intentionally contained substances. They refer to substances allowed within a range that does not adversely affect the martensitic stainless steel material of the present embodiment.

[0141] [Any element]

[0142] The martensitic stainless steel material of the present embodiment may further contain one or more elements selected from the group consisting of Cu, Nb, and Zr in place of a portion of Fe. These elements are arbitrary elements, and all improve the strength of the steel material.

[0143] Cu: 0~3.50%

[0144] Copper (Cu) is an arbitrary element and may not be contained. That is, the Cu content may also be 0%. When contained, Cu improves the hardenability of the steel, thereby improving the yield strength of the steel. As long as a small amount of Cu is contained, the above-mentioned effect can be obtained to some extent. On the other hand, if the Cu content is too high, even if the content of other elements is within the scope of the present embodiment, the hot workability of the steel will also decrease. Thus, the Cu content is 0 to 3.50%. The preferred lower limit of the Cu content exceeds 0%, more preferably 0.01%, more preferably 0.05%, and more preferably 0.10%. The preferred upper limit of the Cu content is 3.30%, more preferably 3.10%, more preferably 2.90%, and more preferably 2.70%. In addition, as described later, the lower limit of the Cu content may also be 0.50%. In this case, the more preferred lower limit of the Cu content is 0.60%, more preferably 0.65%, and more preferably 0.70%. In addition, as described later, the upper limit of the Cu content may also be less than 0.50%. In this case, the upper limit of the Cu content is more preferably 0.45%, further preferably 0.43%, and further preferably 0.40%.

[0145] Nb: 0~0.50%

[0146] Niobium (Nb) is an arbitrary element and may not be contained. That is, the Nb content may also be 0%. When contained, Nb combines with C and / or N to form carbides and / or carbonitrides. As a result, the yield strength of the steel is improved. As long as a small amount of Nb is contained, the above-mentioned effect can be obtained to a certain extent. On the other hand, if the Nb content is too high, even if the content of other elements is within the range of the present embodiment, carbides and / or carbonitrides will be formed excessively, and the corrosion resistance of the steel will decrease. Therefore, the Nb content is 0 to 0.50%. The preferred lower limit of the Nb content exceeds 0%, more preferably 0.01%, and further preferably 0.02%. The preferred upper limit of the Nb content is 0.45%, more preferably 0.40%, further preferably 0.35%, further preferably 0.20%, and further preferably 0.10%.

[0147] Zr: 0~0.050%

[0148] Zirconium (Zr) is an arbitrary element and may not be contained. That is, the Zr content may be 0%. When contained, Zr forms carbides and / or carbonitrides. As a result, the yield strength of the steel is improved. As long as a small amount of Zr is contained, the above-mentioned effect can be obtained to a certain extent. On the other hand, if the Zr content is too high, even if the content of other elements is within the range of the present embodiment, carbides and / or carbonitrides will be formed excessively, and the corrosion resistance of the steel will decrease. Therefore, the Zr content is 0 to 0.050%. The preferred lower limit of the Zr content exceeds 0%, more preferably 0.001%, and further preferably 0.002%. The preferred upper limit of the Zr content is 0.045%, more preferably 0.040%, further preferably 0.030%, further preferably 0.020%, and further preferably 0.010%.

[0149] Furthermore, the martensitic stainless steel material of the present embodiment may contain W in place of a part of Fe.

[0150] W: 0~2.00%

[0151] Tungsten (W) is an arbitrary element and may not be contained. That is, the W content may also be 0%. When contained, W stabilizes the passivation film and improves the corrosion resistance of the steel. As long as a small amount of W is contained, the above-mentioned effect can be obtained to a certain extent. On the other hand, if the W content is too high, even if the content of other elements is within the range of the present embodiment, coarse carbides may sometimes be formed, and the corrosion resistance of the steel may be reduced. Therefore, the W content is 0 to 2.00%. The preferred lower limit of the W content exceeds 0%, more preferably 0.01%, more preferably 0.03%, more preferably 0.05%, and more preferably 0.10%. The preferred upper limit of the W content is 1.70%, more preferably 1.50%, more preferably 1.00%, more preferably 0.60%, more preferably 0.50%, and more preferably 0.40%.

[0152] The martensitic stainless steel material of the present embodiment may further contain one or more elements selected from the group consisting of B and rare earth elements (REM) in place of a portion of Fe. These elements are arbitrary elements and all improve the hot workability of the steel material.

[0153] B: 0~0.0050%

[0154] Boron (B) is an arbitrary element and may not be contained. That is, the B content may also be 0%. When contained, B strengthens the grain boundary and improves the hot workability of the steel. As long as a small amount of B is contained, the above-mentioned effect can be obtained to a certain extent. On the other hand, if the B content is too high, Cr carboboride will be generated even if the content of other elements is within the range of the present embodiment, and the corrosion resistance of the steel will decrease. Therefore, the B content is 0 to 0.0050%. The preferred lower limit of the B content exceeds 0%, more preferably 0.0001%, and further preferably 0.0002%. The preferred upper limit of the B content is 0.0045%, more preferably 0.0040%, and further preferably 0.0035%.

[0155] Rare earth elements (REM): 0~0.0050%

[0156] Rare earth elements (REM) are arbitrary elements and may not be contained. That is, the REM content may also be 0%. When contained, REM controls the morphology of inclusions and improves the hot workability of steel. As long as a small amount of REM is contained, the above-mentioned effect can be obtained to a certain extent. On the other hand, if the REM content is too high, even if the content of other elements is within the range of the present embodiment, coarse oxides will be formed and the corrosion resistance of the steel will decrease. Therefore, the REM content is 0 to 0.0050%. The preferred lower limit of the REM content exceeds 0%, more preferably 0.0001%, further preferably 0.0005%, and further preferably 0.0010%. The preferred upper limit of the REM content is 0.0045%, more preferably 0.0040%, further preferably 0.0035%, and further preferably 0.0025%.

[0157] In addition, REM in this specification refers to one or more elements selected from the group consisting of scandium (Sc) with an atomic number of 21, yttrium (Y) with an atomic number of 39, and lanthanum (La) with an atomic number of 57 to lutetium (Lu) with an atomic number of 71, which are lanthanoid elements. In addition, the REM content in this specification refers to the total content of these elements.

[0158] Preferably, the martensitic stainless steel material of the present embodiment has the above-mentioned chemical composition, and further, the Cu content is 0.50% or more, and the W content is 0.01% or more. In this case, it has better corrosion resistance in a corrosive environment mixed with SOx and NOx. More specifically, in the martensitic stainless steel material of the present embodiment, its chemical composition is C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.030% or less, S: 0.0050% or less, Cr: 11.00-14.00%, Ni: 4.00-7.50%, Mo: 1.50-4.50%, Cu: 0.50-3.50%, Co: 0.01-0.50%, W: 0.01-2.00%, Ti: 0.05-0.30%, V: 0.01-0.50%, and V: 0.01-0.50%. .01~1.00%, Ca: 0.0005~0.0050%, Mg: 0.0005~0.0050%, Al: 0.001~0.100%, N: less than 0.0500%, O: less than 0.0500%, Nb: 0~0.50%, Zr: 0~0.050%, B: 0~0.0050%, rare earth elements: 0~0.0050%, and the balance: Fe and impurities, it has a yield strength of more than 862MPa and better corrosion resistance in a corrosive environment mixed with SOx and NOx.

[0159] In other words, the martensitic stainless steel material of the present embodiment may have the following chemical composition: the chemical composition is, by mass%, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.030% or less, S: 0.0050% or less, Cr: 11.00-14.00%, Ni: 4.00-7.50%, Mo: 1.50-4.50%, Co: 0.01-0.50%, Ti: 0.05-0.30%, V: 0.0005% or less, and the like. .01~1.00%, Ca: 0.0005~0.0050%, Mg: 0.0005~0.0050%, Al: 0.001~0.100%, N: less than 0.0500%, O: less than 0.0500%, Cu: more than 0% and less than 0.50%, Nb: 0~0.50%, Zr: 0~0.050%, W: 0~2.00%, B: 0~0.0050%, rare earth elements: 0~0.0050%, and the balance: Fe and impurities.

[0160] [Formula (1)]

[0161] The martensitic stainless steel material of the present embodiment satisfies the following formula (1) on the premise of having the above chemical composition. As a result, the martensitic stainless steel material of the present embodiment has high strength and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx on the premise of satisfying other characteristics of the present embodiment.

[0162] 0.0010≤Ca+Mg≤0.0050 (1)

[0163] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (1).

[0164] Fn1 (=Ca+Mg) is an index related to Ca oxide and Mg oxide. If Fn1 is too low, Ca and Mg cannot fully fix O as oxide, and a part of O remains in the steel in a solid solution state. On the other hand, if Fn1 is too high, Mg oxide is modified by Ca, and there is a case where the ratio of the number of coarse Mg oxides to the number of specific inclusions decreases. Therefore, in this embodiment, Fn1 is set to 0.0010 to 0.0050 on the premise of having the above chemical composition.

[0165] The preferred lower limit of Fn1 is 0.0012, and more preferably 0.0015. The preferred upper limit of Fn1 is 0.0048, and more preferably 0.0045.

[0166] [Yield Strength]

[0167] The martensitic stainless steel material of the present embodiment has the above chemical composition and satisfies the formula (1), and further, the ratio of the number of coarse Mg oxides to the number of specific inclusions is set to 45.0% or more. As a result, the martensitic stainless steel material of the present embodiment has excellent corrosion resistance in a corrosive environment mixed with SOx and NOx even if it has a yield strength of 862 MPa or more.

[0168] That is, the yield strength of the martensitic stainless steel material of the present embodiment is 862MPa (125ksi) or more. The upper limit of the yield strength is not particularly limited, but the upper limit of the yield strength of the steel material of the present embodiment is, for example, 1034MPa (150ksi). The more preferred upper limit of the yield strength of the steel material is 1000MPa (145ksi). In this specification, the yield strength refers to the 0.2% residual deformation stress (MPa) obtained by a tensile test at room temperature (24±3°C) based on ASTM E8 / E8M (2021) described below.

[0169] Specifically, in the present embodiment, the yield strength is obtained by the following method. First, a tensile test piece is made from the martensitic stainless steel material of the present embodiment. The size of the tensile test piece is not particularly limited. The tensile test piece is, for example, a round bar tensile test piece with a parallel portion diameter of 8.9 mm and a gauge length of 35.6 mm. When the steel material is a steel pipe, the tensile test piece is made from the central part of the wall thickness. In this case, the length direction of the tensile test piece is parallel to the axial direction of the steel pipe. When the steel material is round steel, the tensile test piece is made from the R / 2 position. In addition, in this specification, the R / 2 position of the round steel refers to the central position of the radius R in the cross section perpendicular to the axial direction of the round steel. In addition, in this case, the length direction of the tensile test piece is parallel to the axial direction of the round steel. When the steel material is a steel plate, a tensile test piece is made from the central position of the plate thickness. In this case, the length direction of the tensile test piece is parallel to the rolling direction of the steel plate. Using the prepared tensile test piece, a tensile test was performed at room temperature (24±3° C.) in accordance with ASTM E8 / E8M (2021) to determine the 0.2% residual strain stress (MPa). The determined 0.2% residual strain stress was defined as the yield strength (MPa).

[0170] [Ratio of number of coarse Mg oxides]

[0171] The martensitic stainless steel material of the present embodiment has the above chemical composition and satisfies the formula (1), and further, the ratio of the number of coarse Mg oxides to the number of specific inclusions is 45.0% or more. As a result, the martensitic stainless steel material of the present embodiment has a yield strength of 862 MPa or more and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx.

[0172] As described above, Ca oxides with a circle equivalent diameter of 2.0 μm or more are also referred to as "coarse Ca oxides". In addition, Ca sulfides with a circle equivalent diameter of 2.0 μm or more are also referred to as "coarse Ca sulfides". Furthermore, Mg oxides with a circle equivalent diameter of 2.0 μm or more are also referred to as "coarse Mg oxides". Furthermore, coarse Ca oxides, coarse Ca sulfides, and coarse Mg oxides are also collectively referred to as "specific inclusions".

[0173] Here, coarse Ca oxides are likely to become the starting point of pitting in a corrosive environment mixed with SOx and NOx. Therefore, in the present embodiment, the ratio of coarse Mg oxides in the specific inclusions is increased and the number of coarse Ca oxides is reduced. As a result, excellent corrosion resistance can be obtained even in a corrosive environment mixed with SOx and NOx. Therefore, in the present embodiment, on the premise of having the above chemical composition and satisfying formula (1), the ratio of the number of coarse Mg oxides to the number of specific inclusions is set to 45.0% or more.

[0174] In the present embodiment, the preferred lower limit of the ratio of the number of coarse Mg oxides to the number of specific inclusions is 46.0%, more preferably 48.0%, and further preferably 50.0%. In the present embodiment, the upper limit of the ratio of the number of coarse Mg oxides to the number of specific inclusions is not particularly limited, and may be, for example, 99.0%.

[0175] In the present embodiment, the ratio of the number of coarse Mg oxides to the number of specific inclusions is obtained by the following method. First, the total number density of coarse Ca oxides and coarse Ca sulfides and the number density of coarse Mg oxides are obtained from the martensitic stainless steel material of the present embodiment. Here, in the martensitic stainless steel material of the present embodiment, coarse Ca oxides and coarse Ca sulfides are difficult to be clearly separated. In addition, it is not necessary to obtain the number density of each of coarse Ca oxides and coarse Ca sulfides. Therefore, in the present embodiment, the total number density of coarse Ca oxides and coarse Ca sulfides and the number density of coarse Mg oxides are obtained.

[0176] Specifically, a test piece is made from the martensitic stainless steel material of the present embodiment, with the surface including the rolling direction and the pressing direction as the observation surface. When the steel material is a steel pipe, a test piece is made from the center of the wall thickness, with the surface including the tube axis direction and the wall thickness direction as the observation surface. When the steel material is a round steel, a test piece is made with the surface including the axial direction and the radial direction in its cross section as the observation surface at the center including the R / 2 position. When the steel material is a steel plate, a test piece is made from the center of the plate thickness, with the surface including the rolling direction and the plate thickness direction as the observation surface. The size of the test piece is not particularly limited, for example, it is set to a test piece including an observation surface of 22mm×22mm.

[0177] The prepared test piece is embedded in resin and the observation surface is polished. Observe any 10 fields of view on the polished observation surface. The area of ​​each field of view is, for example, 100 mm. 2 (10mm×10mm). In the observation surface, the particles with a circular equivalent diameter of 2.0μm or more are determined by contrast. The circular equivalent diameter of each particle can be obtained by image analysis. For the particles with a circular equivalent diameter of 2.0μm or more, element concentration analysis (EDS analysis) is performed. In the EDS analysis, the acceleration voltage is set to 20kV, and the target elements are set to N, O, Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Cu, and Nb for quantification.

[0178] Based on the EDS analysis results of each particle, particles having a Ca content of 3% or more, a Mg content of 5% or less, a Ti content of less than 30%, and an Al content of less than 30% by mass% were determined as "coarse Ca oxides or coarse Ca sulfides". Based on the EDS analysis results of each particle, particles having a Mg content of more than 5%, a S content of less than 15%, a Ti content of less than 30%, and an Al content of less than 30% by mass% were further determined as "coarse Mg oxides".

[0179] The total number density (number / cm2) of coarse Ca oxides and coarse Ca sulfides was calculated based on the total number of coarse Ca oxides or coarse Ca sulfides identified in 10 viewing fields and the total area of ​​10 viewing fields. 2 Similarly, the number density of coarse Mg oxides (number / cm) was calculated based on the total number of coarse Mg oxides identified in 10 viewing fields and the total area of ​​10 viewing fields. 2 ) In addition, in the present embodiment, the total number density of coarse Ca oxides and coarse Ca sulfides and the number density of coarse Mg oxides are obtained by rounding off the first decimal place of the obtained numerical values.

[0180] The total number density of coarse Ca oxides and coarse Ca sulfides (number / cm 2) and the number density of coarse Mg oxides (pcs / cm 2 ) is set as the total number density of specific inclusions (inclusive / cm 2 Then, the number density of the obtained coarse Mg oxides (number / cm 2 ) relative to the total number density of specific inclusions (includes / cm 2 ) is defined as the ratio of the number of coarse Mg oxides to the number of specific inclusions (%). In addition, the number density of specific inclusions and coarse Mg oxides can be obtained using a device (SEM-EDS device) that gives a scanning electron microscope a component analysis function. As the SEM-EDS device, for example, the trade name of the inclusion automatic analysis device manufactured by FEI (ASPEX) can be used: Metals Quality Analyzer.

[0181] [Corrosion resistance]

[0182] The martensitic stainless steel material of the present embodiment satisfies the formula (1) on the basis of having the above chemical composition, has a yield strength of 862 MPa or more, and the ratio of the number of coarse Mg oxides to the number of specific inclusions is set to 45.0% or more. As a result, the martensitic stainless steel material of the present embodiment has excellent corrosion resistance in a corrosive environment mixed with SOx and NOx. In the present embodiment, having excellent corrosion resistance in a corrosive environment mixed with SOx and NOx means that in the corrosion rate test under the condition of 150°C described below, the corrosion rate is 0.100 mm / year or less, and no pitting is confirmed.

[0183] Specifically, a corrosion rate test is performed on the martensitic stainless steel material of the present embodiment. Specifically, a test piece for the corrosion rate test is made from the martensitic stainless steel material of the present embodiment. When the steel material is a steel pipe, a test piece is made from the center of the wall thickness. In this case, the length direction of the test piece is parallel to the tube axis direction of the steel pipe. When the steel material is round steel, a test piece is made from the R / 2 position. In this case, the length direction of the test piece is parallel to the axial direction of the round steel. When the steel material is a steel plate, a test piece is made from the center of the plate thickness. In this case, the length direction of the test piece is parallel to the rolling direction of the steel plate. The test piece is, for example, a test piece with a length of 30 mm, a width of 20 mm, and a thickness of 2 mm.

[0184] The test piece was placed in an autoclave, and a 5.0 mass % sodium chloride aqueous solution was injected to immerse the test piece in the 5.0 mass % sodium chloride aqueous solution. A mixed gas of SO2, NO2 and CO2 was pressurized and sealed in the autoclave and the corrosion rate test was started. At this time, the total pressure of the mixed gas was 130 bar, the SO2 concentration in the mixed gas was 10 ppm, and the NO2 concentration in the mixed gas was 10 ppm. In addition, the test time of the corrosion rate test was 96 hours, and the temperature in the autoclave during the test was maintained at 150°C.

[0185] The mass, density and surface area of ​​the test piece after 96 hours are obtained, and the corrosion rate (mm / year) of the test piece is obtained. In addition, in the present embodiment, the corrosion rate is obtained by rounding off the fourth decimal place of the obtained value. And, the surface of the test piece after 96 hours is observed with a magnifying glass with a magnification of 10 times to confirm whether there is pitting. In the case of doubts about the occurrence of pitting during observation using a magnifying glass, further observation is performed using an optical microscope with a magnification of 100 times to confirm whether there is pitting. In the present embodiment, when the corrosion rate obtained is less than 0.100 mm / year and no pitting is confirmed, it is judged that the steel has excellent corrosion resistance in a corrosive environment mixed with SOx and NOx.

[0186] As described above, the martensitic stainless steel material of the present embodiment has better corrosion resistance in a corrosive environment mixed with SOx and NOx when it not only contains the above chemical composition but also satisfies the Cu content: 0.50-3.50% and the W content: 0.01-2.00%. In the present embodiment, having better corrosion resistance in a corrosive environment mixed with SOx and NOx means that in a corrosion rate test under 175°C, the corrosion rate is 0.100 mm / year or less and no pitting is confirmed. Specifically, in the above corrosion rate test, the temperature in the autoclave is set to 175°C, and the corrosion rate test is performed under the above conditions. As a result, when the obtained corrosion rate is 0.100 mm / year or less and no pitting is confirmed, it is judged that the steel material has better corrosion resistance in a corrosive environment mixed with SOx and NOx.

[0187] [Microstructure]

[0188] The microstructure of the martensitic stainless steel material of the present embodiment is mainly composed of martensite. In this specification, "mainly composed of martensite" means that the microstructure is composed of 0-5% retained austenite and 0-5% ferrite by volume, and the balance is martensite. In this specification, "composed of retained austenite, ferrite and martensite" means that the phases other than retained austenite, ferrite and martensite are so small that they can be ignored. For example, in the chemical composition of the martensitic stainless steel material of the present embodiment, the volume ratio of precipitates and inclusions is so small as to be ignored compared with the volume ratio of retained austenite, ferrite and martensite. That is, in the microstructure of the martensitic stainless steel material of the present embodiment, in addition to retained austenite, ferrite and martensite, trace amounts of precipitates, inclusions, etc. may also be contained.

[0189] If the microstructure of the steel material having the above chemical composition is mainly composed of martensite, it has a yield strength of 862 MPa or more and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx, provided that the other characteristics of the present embodiment are met. Therefore, in the present embodiment, on the basis of having the above chemical composition and satisfying the other characteristics of the present embodiment, while having a yield strength of 862 MPa or more and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx, it is judged that the microstructure of the steel material is composed of 0-5% of retained austenite and 0-5% of ferrite by volume, and the balance is martensite.

[0190] In addition, when the microstructure of the steel material is determined by observation, the following method can be used. In this case, specifically, the volume fraction (%) of martensite in the microstructure of the steel material is obtained by subtracting the volume fraction (%) of retained austenite obtained by the method shown below and the volume fraction (%) of ferrite obtained by the method shown below from 100%.

[0191] [Method for measuring the volume fraction of retained austenite]

[0192] The volume fraction of retained austenite in the microstructure of the steel is determined by X-ray diffraction. Specifically, a test piece for measuring the volume fraction of retained austenite is made from the steel of the present embodiment. When the steel is a steel pipe, a test piece is collected from the center of the wall thickness. When the steel is a round steel, a test piece is collected from the R / 2 position. When the steel is a steel plate, a test piece is collected from the center of the plate thickness. There is no particular restriction on the size of the test piece. The test piece is, for example, 15 mm × 15 mm × thickness 2 mm. When the steel is a steel pipe, the thickness direction of the test piece is the pipe diameter direction. When the steel is a round steel, the thickness direction of the test piece is the radial direction. When the steel is a steel plate, the thickness direction of the test piece is the plate thickness direction. Using the prepared test specimens, the X-ray diffraction intensities of the (110) plane of the α phase (martensite), the (200) plane of the α phase, the (211) plane of the α phase, the (111) plane of the γ phase (retained austenite), the (200) plane of the γ phase, and the (220) plane of the γ phase were measured, and the integrated intensity of each plane was calculated.

[0193] In the measurement of X-ray diffraction intensity, the target of the X-ray diffraction device was set to Co (Co-Kα ray) and the output was set to 30 kV-100 mA. The measurement angle (2θ) was set to 45° to 105°. After calculation, the volume fraction Vγ (%) of retained austenite was calculated for each combination of each face of the α phase and each face of the γ phase (3×3=9 groups) using formula (I). Then, the average value of the volume fraction Vγ of the 9 groups of retained austenite was defined as the volume fraction (%) of retained austenite.

[0194] Vγ=100 / {1+(Iα×Rγ) / (Iγ×Rα)}(I)

[0195] Among them, Iα is the integrated intensity of the α phase. Rα is the crystallographically calculated value of the α phase. Iγ is the integrated intensity of the γ phase. Rγ is the crystallographically calculated value of the γ phase. The values ​​of Rα and Rγ in each surface can be the values ​​entered in the residual γ quantitative analysis system attached to the product name RINT-TTR manufactured by Rigaku Corporation. In addition, the volume fraction of retained austenite is obtained by rounding off the first decimal place of the obtained value.

[0196] [Method for measuring the volume fraction of ferrite]

[0197] The volume fraction of ferrite in the microstructure of the steel is determined by the point counting method. Specifically, a test piece for measuring the volume fraction of ferrite is made from the steel of the present embodiment. When the steel is a steel pipe, the test piece is collected from the center of the wall thickness. When the steel is a round steel, the test piece is collected from the R / 2 position. When the steel is a steel plate, the test piece is collected from the center of the plate thickness. In addition, the size of the test piece is not particularly limited. In addition, when the steel is a steel pipe, the observation surface of the test piece is a surface parallel to the axial direction of the steel pipe. When the steel is a round steel, the observation surface of the test piece is a surface parallel to the axial direction of the round steel. When the steel is a steel plate, the observation surface of the test piece is a surface parallel to the rolling direction of the steel plate. After mechanically grinding the observation surface, the observation surface is electrolytically etched to expose the structure. Electrolytic etching is performed with an electrolyte: 30% sodium hydroxide aqueous solution, a current density: 1A / cm 2 , Electrolysis time: 1 minute.

[0198] The observation surface after electrolytic etching was observed in 30 fields of view using an optical microscope. The observation field was set to a rectangle of 250 μm × 250 μm. In addition, the observation magnification was 400 times. In each observation field, a person skilled in the art can distinguish ferrite from other phases (retained austenite, martensite) based on contrast. Therefore, the ferrite in each observation field is determined based on contrast. The area ratio of the determined ferrite is obtained by the point counting method based on ASTM E562 (2019).

[0199] Specifically, for the observation field, 20 vertical lines are drawn at equal intervals from the upper end to the lower end of the observation field. That is, the observation field is divided into 21 areas in the left and right directions by 20 vertical lines. Further, for the observation field, 20 horizontal lines are drawn at equal intervals from the left end to the right end of the observation field. That is, the observation field is divided into 21 areas in the up and down directions by 20 horizontal lines. At this time, the intersection of the vertical line and the horizontal line is called a lattice point. That is, 400 lattice points are arranged at equal intervals in the observation field. According to ASTM E562 (2019), the lattice points overlapping with ferrite are counted in the observation field. The number of lattice points overlapping with ferrite obtained in 30 fields of view is divided by the total number of lattice points (400×30=12000) and defined as the ferrite area ratio. In this embodiment, the area ratio of ferrite obtained by the above method is regarded as the volume ratio (%) of ferrite. In addition, the volume fraction of ferrite is obtained by rounding off the first decimal place of the obtained numerical value.

[0200] The volume fraction (%) of martensite in the microstructure of the steel material is calculated by the following formula using the volume fraction (%) of retained austenite obtained by the above X-ray diffraction method and the volume fraction (%) of ferrite obtained by the above point counting method.

[0201] Volume fraction of martensite (%) = 100.0 - {volume fraction of retained austenite (%) + volume fraction of ferrite (%)}

[0202] As described above, the martensitic stainless steel material of the present embodiment has the above-mentioned chemical composition and satisfies the formula (1), has a yield strength of 862 MPa or more, and makes the ratio of the number of coarse Mg oxides to the number of specific inclusions 45.0% or more. As a result, the martensitic stainless steel material of the present embodiment has high strength and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx.

[0203] [Any feature]

[0204] The martensitic stainless steel material of the present embodiment may also have the features described below. That is, the features described below are arbitrary features in the martensitic stainless steel material of the present embodiment.

[0205] [Total number density of specific inclusions]

[0206] The martensitic stainless steel material of the present embodiment has the above chemical composition, satisfies the above formula (1), has a yield strength of 862 MPa or more, satisfies the ratio of the number of coarse Mg oxides to the number of specific inclusions of 45.0% or more, and under this premise, the total number density of specific inclusions may be 1000 / cm 2 The martensitic stainless steel material of the present embodiment satisfies the requirement that the total number density of specific inclusions is 1000 / cm 2 In the above circumstances, the martensitic stainless steel material of the present embodiment has not only high strength and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx, but also excellent hot workability.

[0207] In the steel material having the above chemical composition, when Ca and Mg are used to fix O or S, oxides are preferentially formed, and S tends to remain in a solid solution state. On the other hand, if the total number density of specific inclusions is increased, the solid solution amount of S can be reduced, and the hot workability of the steel material becomes higher. Therefore, in the martensitic stainless steel material of this embodiment, it is preferred that the total number density of specific inclusions is 1000 / cm 2 above.

[0208] In this embodiment, the more preferred lower limit of the total number density of specific inclusions is 1050 pieces / cm 2 , more preferably 1100 pcs / cm 2 , more preferably 1150 pcs / cm 2 In this embodiment, the upper limit of the total number density of specific inclusions is not particularly limited, and may be, for example, 3000 / cm2 .

[0209] The total number density of coarse Ca oxides and coarse Ca sulfides and the number density of coarse Mg oxides are not particularly limited. The total number density of coarse Ca oxides and coarse Ca sulfides may be, for example, 10 to 1500 pieces / cm 2 , can also be 30 to 1250 pieces / cm 2 , and can also be 50 to 1000 pieces / cm 2 The number density of coarse Mg oxides can be, for example, 450 to 3000 per cm 2 , or 500 to 2500 pcs / cm 2 , and can also be 600 to 2000 pieces / cm 2 .

[0210] [Formula (2)]

[0211] The martensitic stainless steel material of the present embodiment has the above chemical composition, satisfies the above formula (1), has a yield strength of 862 MPa or more, satisfies the ratio of the number of coarse Mg oxides to the number of specific inclusions of 45.0% or more, and under this premise, can also satisfy the following formula (2). When the martensitic stainless steel material of the present embodiment satisfies the formula (2), the total number density of specific inclusions can be stably increased to 1000 / cm 2 above.

[0212] Ca / S≥0.80 (2)

[0213] Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (2).

[0214] It is defined as Fn2 = Ca / S. Fn2 is an index related to Ca sulfide. By increasing Fn2, Ca can sufficiently fix S as Ca sulfide. As a result, the total number density of specific inclusions can be stably increased. Therefore, in the martensitic stainless steel material of the present embodiment, it is preferred that Fn2 be set to 0.80 or more, provided that the above chemical composition is present and the above formula (1) is satisfied.

[0215] The more preferred lower limit of Fn2 is 0.85, further preferably 0.90, and further preferably 1.00. The upper limit of Fn2 is not particularly limited, and may be, for example, 20.00, 15.00, or 10.00.

[0216] [Hot workability]

[0217] Preferably, the martensitic stainless steel material of the present embodiment satisfies the formulas (1) and (2) while having the above chemical composition, has a yield strength of 862 MPa or more, has a ratio of the number of coarse Mg oxides to the number of specific inclusions of 45.0% or more, and has a total number density of 1000 inclusions / cm 2 As a result, the martensitic stainless steel material of the present embodiment has not only high strength and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx, but also excellent hot workability. In the present embodiment, having excellent hot workability means that the necking value Ra obtained by the hot workability test described below is 70% or more.

[0218] The hot workability test (Greeble test) is performed on the martensitic stainless steel material of the present embodiment. Specifically, a test piece for the Greeble test is made from a billet obtained in the manufacturing process of the martensitic stainless steel material of the present embodiment. The billet may be a cast billet or an ingot, and the cast billet may be a billet, a large steel bloom, or a slab. It is preferred to use a cast billet or an ingot that has been subjected to hot forging and initial rolling.

[0219] In this embodiment, the position of the test piece for the Greeble test made from the billet is not particularly limited, but it is made to avoid the center of the billet where segregation and defects are easily generated during solidification. The test piece is, for example, a round bar test piece with a diameter of 10 mm and a length of 130 mm. The length direction of the test piece is parallel to the direction in which the billet is subjected to hot working. For example, when the billet is a round billet and piercing and rolling are performed as hot working, the length direction of the test piece is parallel to the axial direction (rolling direction) of the round billet.

[0220] For the test piece heated to 900℃, the strain rate was 10s -1 A tensile test is performed to break the test piece. The necking value Ra (%) is obtained from the broken test piece. In addition, in the present embodiment, the necking value Ra is obtained by rounding off the first decimal place of the obtained value. In the present embodiment, when the obtained necking value Ra is 70% or more, it is judged that the steel material has excellent hot workability.

[0221] [Shapes and uses of steel]

[0222] As described above, the shape of the martensitic stainless steel material of the present embodiment is not particularly limited. Specifically, the martensitic stainless steel material of the present embodiment may be a steel pipe, round steel (solid material), or a steel plate. In addition, the steel pipe may be a seamless steel pipe or a welded steel pipe. The martensitic stainless steel material of the present embodiment is suitable for storage technology applications of CCUS, for example.

[0223] [Manufacturing method]

[0224] An example of a method for manufacturing a martensitic stainless steel material of the present embodiment is described. In addition, the manufacturing method described below is an example, and the manufacturing method of the martensitic stainless steel material of the present embodiment is not limited to the following description. That is, as long as the martensitic stainless steel of the present embodiment having the above-mentioned characteristics can be manufactured, it is not limited to the manufacturing method described below. However, the manufacturing method described below is a suitable manufacturing method for manufacturing the martensitic stainless steel material of the present embodiment.

[0225] An example of a method for manufacturing a martensitic stainless steel material of the present embodiment includes: a step of preparing a billet (steel making step); a step of hot working the billet to manufacture an intermediate steel material (hot working step); and a step of quenching and tempering the intermediate steel material (heat treatment step). Each step is described in detail below.

[0226] [Steelmaking process]

[0227] The steelmaking process includes a process of producing molten steel (refining process) and a process of producing a billet by casting using the molten steel (billet production process).

[0228] [Refining process]

[0229] In the refining process, first, the molten steel containing Cr is placed in a ladle, and the molten steel in the ladle is decarburized under atmospheric pressure (rough decarburization refining process). Slag is generated by the decarburization in the rough decarburization refining process. Slag generated by the decarburization floats on the liquid surface of the molten steel after the rough decarburization refining process. In the rough decarburization refining process, the Cr in the molten steel is oxidized to generate Cr2O3. Cr2O3 is absorbed into the slag. Therefore, a deoxidizer is added to the ladle to reduce the Cr2O3 in the slag and recover Cr into the molten steel (Cr reduction treatment process). The rough decarburization refining process and the Cr reduction treatment process are implemented, for example, by an electric furnace method, a converter method, or an argon oxygen decarburization (AOD, Argon Oxygen Decarburization) method. After the Cr reduction treatment process, the slag is removed from the molten steel (slag removal treatment process).

[0230] The molten steel after the slag removal treatment step is further subjected to a final decarburization treatment (final decarburization refining step). After the final decarburization refining step, a deoxidizer is added to the molten steel, and a Cr reduction treatment (Cr reduction treatment step) is performed again to reduce Cr2O3 in the slag. The final decarburization refining step and the Cr reduction treatment step after the final decarburization refining step are performed, for example, by a vacuum oxygen decarburization (VOD) method, or by a RH (Ruhrstahl-Heraeus) method.

[0231] After the Cr reduction treatment step, the molten steel in the ladle is subjected to final composition adjustment and temperature adjustment of the molten steel before the billet manufacturing step (composition adjustment step). The composition adjustment step can be performed, for example, by ladle treatment (LT, Ladle Treatment). In the composition adjustment step of this embodiment, the temperature of the molten steel in the ladle is preferably maintained at 1500-1700°C.

[0232] In the composition adjustment process of the present embodiment, it is preferred to implement the addition of elements in the following order. Specifically, Mg is added to molten steel to form coarse Mg oxides in the molten steel. Thereafter, it is preferred to add Ca to the molten steel to form coarse Ca sulfides. Here, Ca is stronger than Mg in terms of deoxidation power in molten steel. Therefore, in the case where Mg is added to the molten steel after Ca is added to the molten steel to form coarse Ca oxides, coarse Mg oxides are sometimes not sufficiently formed. In this case, in the manufactured martensitic stainless steel, the ratio of the number of coarse Mg oxides to the number of specific inclusions is reduced, and excellent corrosion resistance in a corrosive environment mixed with SOx and NOx cannot be obtained. Therefore, in the composition adjustment process of the present embodiment, it is preferred to add Ca after adding Mg to the molten steel.

[0233] In the composition adjustment process of the present embodiment, it is preferred that after adding Mg to the molten steel, the timing of adding Ca and the timing of tapping after adding Ca are controlled. Specifically, the time from adding the element component to the molten steel until the element component added to the molten steel is uniformly dispersed is defined as "uniform mixing time" τ. The uniform mixing time τ can be calculated by the following formula (A).

[0234] τ=800×ε -0.4 (A)

[0235] Here, ε is the stirring power density of molten steel in LT, and is defined by formula (B).

[0236] ε=28.5(Q / W)×T×log(1+H / 1.48)(B)

[0237] Here, Q is the top blowing gas flow rate (Nm 3 / min). W is the mass of molten steel (t). T is the temperature of molten steel (K). H is the depth of molten steel in the ladle (molten steel depth) (m).

[0238] In the present specification, in the composition adjustment process, the time from when Mg is added to the molten steel and the uniform mixing time τ has passed until Ca is added is defined as "holding time tA" (seconds). In the present specification, the time from when Ca is added to the molten steel and the uniform mixing time τ has passed until steel is tapped is defined as "holding time tB" (seconds). Preferably, in the composition adjustment process of the present embodiment, the holding time tA (seconds) and the holding time tB (seconds) satisfy the following formula (C).

[0239] tA / tB>1.0(C)

[0240] Defined as FnC = tA / tB. FnC is an indicator of the state of oxide-based inclusions in molten steel. When FnC is small, Mg oxides are sometimes not fully formed. When FnC is small, Mg oxides are sometimes excessively modified by Ca oxides, thereby reducing Mg oxides in the molten steel. When FnC is small, Ca oxides and / or Ca sulfides are sometimes coarsened, and Ca oxides and / or Ca sulfides in the molten steel are reduced. In these cases, in the manufactured martensitic stainless steel, the ratio of the number of coarse Mg oxides to the number of specific inclusions is reduced, and sometimes excellent corrosion resistance in a corrosive environment mixed with SOx and NOx cannot be obtained. In these cases, in the manufactured martensitic stainless steel, the total number density of specific inclusions is sometimes reduced.

[0241] Therefore, in the composition adjustment process of the present embodiment, it is preferred that FnC exceeds 1.0. In this case, in the manufactured martensitic stainless steel, the ratio of the number of coarse Mg oxides to the number of specific inclusions can be stably increased. In addition, there is no particular limitation on FnC, and for example, it may be 10.0. In addition, if FnC exceeds 1.0, there is no particular limitation on the holding time tA from the time Mg is added to the molten steel and the uniform mixing time τ is passed until Ca is added, and the holding time tB from the time Ca is added to the molten steel and the uniform mixing time τ is passed until steel is tapped. The holding time tA may be, for example, 120 to 600 seconds. The holding time tB may be, for example, 60 seconds or more and less than 120 seconds. The following is a description of the billet manufacturing process.

[0242] [Blank material manufacturing process]

[0243] The molten steel produced by the above refining process is used to produce a billet (cast billet or ingot). Specifically, the cast billet is produced by continuous casting using the molten steel. The cast billet may be a slab, a large bloom, or a billet. Alternatively, the molten steel may be used to produce an ingot by an ingot casting process. The cast billet or the ingot may also be further subjected to initial rolling to produce a billet. The billet is produced by the above process. The hot working process is described in detail below.

[0244] [Hot working process]

[0245] In the hot working process, the billet is hot worked to produce an intermediate steel product. When the steel product is a seamless steel pipe, the intermediate steel product is equivalent to a pipe blank. When the steel product is a seamless steel pipe, first, the billet is heated in a heating furnace. The heating temperature is not particularly limited, and is, for example, 1100 to 1300°C. The billet taken out of the heating furnace is hot worked to produce a pipe blank (seamless steel pipe). The hot working method is not particularly limited, and can be a known method.

[0246] For example, the Mannesmann method can be implemented as hot working to produce a tube blank. In this case, the round steel billet is pierced and rolled by a piercer. In the case of piercing and rolling, the piercing ratio is not particularly limited, and is, for example, 1.0 to 4.0. The round steel billet that has been pierced and rolled is hot rolled by a mandrel mill, a reducing mill, a sizing mill, etc. to produce a tube blank. The cumulative cross-sectional reduction rate in the hot working process is, for example, 20 to 70%.

[0247] Other hot working methods may be used to produce a tube blank from a steel billet. For example, when the steel material is a short thick-walled steel pipe such as a coupling, the tube blank may be produced by forging such as the Ehrlich process. The tube blank is produced by the above process. The wall thickness of the tube blank is not particularly limited, and is, for example, 9 to 60 mm.

[0248] In the case where the steel material is round steel, the billet is first heated in a heating furnace. The heating temperature is not particularly limited, and is, for example, 1100 to 1300°C. The billet taken out of the heating furnace is subjected to hot working to produce an intermediate steel material having a circular cross section perpendicular to the axial direction. Hot working is, for example, initial rolling using a preliminary rolling mill or hot rolling using a continuous rolling mill. In a continuous rolling mill, a horizontal stand having a pair of hole-shaped rollers arranged in an up-and-down direction and a vertical stand having a pair of hole-shaped rollers arranged in a horizontal direction are alternately arranged.

[0249] When the steel material is a steel plate, the billet is first heated in a heating furnace. The heating temperature is not particularly limited, and is, for example, 1100 to 1300° C. The billet taken out of the heating furnace is hot rolled using a blooming mill and a tandem mill to produce an intermediate steel material in the shape of a steel plate.

[0250] The intermediate steel produced by hot working can be air-cooled (As-Rolled). The intermediate steel produced by hot working can also be directly quenched after hot working without cooling to room temperature, or can be quenched after supplementary heating (reheating) after hot working.

[0251] When direct quenching is performed after hot working, or quenching is performed after supplementary heating, cooling can be stopped during the quenching process, or slow cooling can be performed. In this case, the generation of quenching cracks in the intermediate steel can be suppressed. When direct quenching is performed after hot working, or quenching is performed after supplementary heating, stress relief annealing (SR) can be performed after quenching and before the heat treatment of the next process. In this case, the residual stress of the intermediate steel is eliminated. The heat treatment process is described in detail below.

[0252] [Heat treatment process]

[0253] The heat treatment process includes a quenching process and a tempering process.

[0254] [Quenching process]

[0255] In the heat treatment process, first, the intermediate steel material manufactured by the hot working process is quenched (quenching process). Quenching is carried out by a known method. Specifically, the intermediate steel material after the hot working process is loaded into a heat treatment furnace and maintained at a quenching temperature. The quenching temperature is above the A3 point, for example, 900 to 1000°C. The intermediate steel material is maintained at the quenching temperature and then rapidly cooled (quenched). The holding time at the quenching temperature is not particularly limited, for example, 10 to 60 minutes. The quenching method is, for example, water cooling. The quenching method is not particularly limited. For example, in the case where the intermediate steel material is a tube billet, the tube billet can be immersed in a water tank or an oil tank to rapidly cool the tube billet, or the cooling water can be poured or sprayed onto the outer surface and / or inner surface of the tube billet by spray cooling or spray cooling to rapidly cool the tube billet.

[0256] In addition, as described above, after the hot working process, quenching (direct quenching) can be performed immediately after the hot working without cooling the intermediate steel material to room temperature, or the intermediate steel material after the hot working can be loaded into a supplementary heating furnace before the temperature drops, thereby maintaining the quenching temperature and then performing quenching.

[0257] [Tempering process]

[0258] The intermediate steel material after quenching is further subjected to a tempering process. In the tempering process, the yield strength of the steel material is adjusted. In the present embodiment, the tempering temperature is set to 540 to 620°C. The holding time at the tempering temperature (tempering time) is not particularly limited, and is, for example, 10 to 180 minutes. Here, the tempering temperature refers to the temperature of the heat treatment furnace for performing tempering. In addition, the tempering time refers to the time during which the intermediate steel material is maintained at the tempering temperature. In addition, it is well known to those skilled in the art that the yield strength of the steel material can be adjusted by appropriately adjusting the tempering temperature according to the chemical composition. That is, in the present embodiment, the tempering conditions are adjusted so that the yield strength of the steel material is above 862MPa.

[0259] Through the above steps, the martensitic stainless steel material of the present embodiment can be manufactured. In addition, as described above, the martensitic stainless steel material of the present embodiment is not limited to the above manufacturing method. Specifically, as long as a martensitic stainless steel material having the above chemical composition, satisfying formula (1), having a yield strength of 862 MPa or more, and a ratio of the number of coarse Mg oxides to the number of specific inclusions of 45.0% or more can be manufactured, the manufacturing method of the present embodiment is not limited to the above manufacturing method. The martensitic stainless steel material of the present embodiment is described in more detail below through examples.

[0260] Example 1

[0261] Molten steel having the chemical composition shown in Table 1-1 and Table 1-2 is manufactured. In Table 1-2, "-" means that the content of the element is at the level of an impurity. For example, the Cu, Nb and W contents of Test No. 1 refer to the case where the third decimal place is rounded off to 0%. The Zr content of Test No. 1 refers to the case where the fourth decimal place is rounded off to 0%. The B and REM contents of Test No. 1 refer to the case where the fifth decimal place is rounded off to 0%. In addition, Fn1 and Fn2 obtained from the chemical composition of each test number recorded in Table 1-1 and Table 1-2 and the above definition are shown in Table 2.

[0262] [Table 1-1]

[0263] Table 1-1

[0264]

[0265] [Table 1-2]

[0266] Table 1-2

[0267]

[0268] [Table 2]

[0269] surface

[0270]

[0271] Molten steel of each test number was produced as follows. Molten steel containing Cr was placed in a ladle, and a known rough decarburization refining step and a Cr reduction treatment step were performed by the AOD method. After the Cr reduction treatment step, a deslagging treatment step of removing slag from the molten steel was performed. Then, a known final decarburization refining step and a Cr reduction treatment step were performed by the VOD method.

[0272] After the Cr reduction treatment process by the VOD method, the molten steel in the ladle was subjected to final composition adjustment by LT. At this time, for the molten steel to which Ca was added after Mg, it was marked as "A (Acceptable)" in the "Mg-Ca addition order" column in Table 2. On the other hand, for the molten steel to which Mg was added after Ca was added, it was marked as "NA (Not Acceptable)" in the "Mg-Ca addition order" column in Table 2.

[0273] In addition, in each test number other than test number 26, the holding time tA (seconds) from the addition of Mg and the uniform mixing time τ to the addition of Ca was adjusted as shown in Table 2. In each test number other than test number 26, the holding time tB (seconds) from the addition of Ca and the uniform mixing time τ to the tapping of steel was adjusted as shown in Table 2. In addition, in test number 26, the time from the addition of Ca and the uniform mixing time τ to the addition of Mg is shown in Table 2 as the holding time tA (seconds). In test number 26, the time from the addition of Mg and the uniform mixing time τ to the tapping of steel is shown in Table 2 as the holding time tB (seconds). In addition, in each test number, FnC (= tA / tB) calculated from the holding time tA (seconds), the holding time tB (seconds) and the above formula (C) is shown in Table 2. Through the above steps, molten steel with the chemical composition shown in Tables 1-1 and 1-2 was produced.

[0274] From the molten steel of each test number produced, steel ingots are produced by the ingot casting method. The steel ingots of each test number are heated at 1250°C for 3 hours. The heated steel ingots are hot forged to produce multiple blocks for each test number. One block of each test number is hot rolled. Specifically, after the blocks of each test number after hot forging are heated at 1230°C for 3 hours, hot rolling is performed. Thus, steel materials (steel plates) of each test number with a thickness of 13 mm are produced.

[0275] The steel materials of each test number were quenched. Specifically, the steel plates of each test number were kept at 910°C for 15 minutes and then water-cooled. The steel plates of each test number after quenching were tempered at the tempering temperature (°C) recorded in Table 2 for the tempering time (minutes) recorded in Table 2. The steel plates of each test number were manufactured through the above manufacturing process.

[0276] [Evaluation test]

[0277] The produced steel plates of each test number were subjected to a tensile test, a specific inclusion number measurement test, a hot workability test, and a corrosion resistance test.

[0278] [Tensile test]

[0279] For the steel plates of each test number, tensile tests were performed in accordance with ASTM E8 / E8M (2021). Specifically, a round bar tensile test piece with a diameter of 8.9 mm and a gauge length of 35.6 mm in the parallel portion was made from the central position of the plate thickness of the steel plate of each test number. The length direction of the round bar tensile test piece is parallel to the rolling direction of the steel plate. Using the round bar tensile test piece of each test number, a tensile test was performed in the atmosphere at room temperature (24±3°C) to determine the 0.2% residual deformation stress (MPa). The determined 0.2% residual deformation stress is defined as the yield strength (MPa). The yield strength of each test number obtained is shown in the "YS (MPa)" column of Table 3.

[0280] [Table 3]

[0281] Table 3

[0282]

[0283] [Specific inclusion count measurement test]

[0284] For the steel plates of each test number, the total number density (number / cm2) of Ca oxides (coarse Ca oxides) with a circle equivalent diameter of 2.0 μm or more and Ca sulfides (coarse Ca sulfides) with a circle equivalent diameter of 2.0 μm or more was determined by the above method. 2 ), and the number density (pcs / cm2) of Mg oxides with a circle equivalent diameter of 2.0 μm or more (coarse Mg oxides) 2 The total number density of coarse Ca oxides and coarse Ca sulfides obtained for each test number is shown in "Ca(O,S) (number / cm 2 The number density of coarse Mg oxides obtained for each test number is shown in the "MgO (pieces / cm 2 The total number density of coarse Ca oxides, coarse Ca sulfides and coarse Mg oxides for each test number is shown in the "Specific inclusions (individuals / cm 2 In addition, the ratio of the number of coarse Mg oxides to the number of specific inclusions in each test number is shown in the "MgO ratio (%)" column of Table 3.

[0285] [Hot workability test]

[0286] For the blocks of each test number, a hot workability test (Greeble test) was implemented by the above method. In addition, as mentioned above, the blocks of each test number refer to blocks obtained by hot forging the steel ingots manufactured by the molten steel of each test number. Round bar test pieces are made from the blocks of each test number. Specifically, for the blocks of each test number, the direction of hot rolling (equivalent to the rolling direction of the manufactured steel plate) is determined. In addition, the surface of the block of each test number, the surface where hot rolling is implemented (the surface perpendicular to the plate thickness direction of the steel plate) is determined. In the cross section perpendicular to the direction where hot rolling is implemented (rolling direction of the steel plate) of the block of each test number, a round bar test piece is made from the intersection of two diagonals and the center position of the surface where hot rolling is implemented.

[0287] The round bar test piece has a diameter of 10 mm and a length of 130 mm. The length direction of the round bar test piece is parallel to the direction in which the block is hot rolled (rolling direction of the steel plate). After heating the round bar test piece of each test number to 900°C, the strain rate was 10s -1 A tensile test was performed to break the round bar test piece of each test number. The neck shrinkage value Ra (%) was determined from the broken round bar test piece of each test number. The obtained neck shrinkage value Ra of each test number is shown in the "Ra (%)" column of Table 3.

[0288] [Corrosion resistance test]

[0289] For the steel plates of each test number, the corrosion resistance test (corrosion rate test) was carried out in the above-mentioned method. Specifically, a test piece with a length of 30 mm, a width of 20 mm, and a thickness of 2 mm was made from the center of the plate thickness of the steel plates of each test number. Among them, the length direction of the test piece is parallel to the rolling direction. The test pieces of each test number were immersed in a 5.0 mass % sodium chloride aqueous solution in an autoclave. In the autoclave, a mixed gas (SO2, NO2 and CO2) with a total pressure of 130 bar, a SO2 concentration of 10 ppm, and a NO2 concentration of 10 ppm was pressurized and sealed. The temperature in the autoclave was maintained at 150°C, and a corrosion rate test was carried out for 96 hours.

[0290] For the test piece after 96 hours, the corrosion rate (mm / year) was calculated from the mass, density and surface area. For the test piece after 96 hours, a magnifying glass with a magnification of 10 times and an optical microscope with a magnification of 100 times were also used to observe the presence or absence of pitting. When the obtained corrosion rate is less than 0.100 mm / year and no pitting is confirmed, it is judged to have excellent corrosion resistance in a corrosive environment mixed with SOx and NOx ("EX (Excellent)" in the "Corrosion Resistance (150°C)" column in Table 3). On the other hand, when the obtained corrosion rate exceeds 0.100 mm / year or pitting is confirmed, it is judged not to have excellent corrosion resistance in a corrosive environment mixed with SOx and NOx ("NA (Not Acceptable)" in the "Corrosion Resistance (150°C)" column in Table 3). The evaluation of corrosion resistance of each test number is shown in Table 3.

[0291] [Evaluation results]

[0292] Referring to Table 1-1, Table 1-2, Table 2 and Table 3, the chemical composition of the steel plates of test numbers 1 to 19 is appropriate, and Fn1 is 0.0010 to 0.0050. These steel plates also have a yield strength of 862 MPa or more. In these steel plates, the ratio of the number of coarse Mg oxides to the number of specific inclusions is 45.0% or more. As a result, these steel plates have excellent corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test. In addition, based on these evaluation results, it is judged that these steel plates have a microstructure composed of 0 to 5% retained austenite, 0 to 5% ferrite, and the balance is martensite by volume.

[0293] The steel sheets of test numbers 1 to 16 also had Fn2 of 0.80 or more, and were manufactured by the above-mentioned preferred manufacturing method. As a result, the total number density of specific inclusions in these steel sheets was 1000 pieces / cm 2 As a result, these steel sheets had neck reduction values ​​Ra of 70% or more in the hot workability test, showing excellent hot workability.

[0294] On the other hand, the Fn1 of the steel sheets of test numbers 20 and 21 was too high. As a result, in these steel sheets, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, these steel sheets did not show excellent corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0295] The Ca contents of the steel sheets of test numbers 22 and 23 were too low.

[0296] The Mg content of the steel sheet of test number 24 was too low. As a result, in the steel sheet, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, the steel sheet did not show excellent corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0297] In the steel sheet of test number 25, the Ca content was too low, the Mg content was too low, and Fn1 was too low.

[0298] In the steel plate of test number 26, Mg was added after Ca was added when the molten steel was produced. As a result, in the steel plate, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, the steel plate did not show excellent corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0299] In the steel plate of test number 27, FnC was too small when molten steel was produced. As a result, in the steel plate, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, the steel plate did not show excellent corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0300] Example 2

[0301] In Example 2, the effect of the martensitic stainless steel material of the present embodiment was confirmed when the Cu content was 0.50% or more and the W content was 0.01% or more. Specifically, molten steel having the chemical composition shown in Table 4-1 and Table 4-2 was produced. Among them, "-" in Table 4-2 means that the content of the element is an impurity. For example, for the Nb content of Test No. 1, it refers to the case where the third decimal place is rounded off to 0%. For the Zr content of Test No. 1, it refers to the case where the fourth decimal place is rounded off to 0%. For the B and REM contents of Test No. 1, it refers to the case where the fifth decimal place is rounded off to 0%. In addition, the chemical composition of each test number recorded in Table 4-1 and Table 4-2 and Fn1 and Fn2 obtained by the above definition are shown in Table 5.

[0302] [Table 4-1]

[0303] Table 4-1

[0304]

[0305] [Table 4-2]

[0306] Table 4-2

[0307]

[0308] [Table 5]

[0309] Table 5

[0310]

[0311] Molten steel of each test number was produced in the same manner as in Example 1. Molten steel containing Cr was placed in a ladle, and a known rough decarburization refining step and a Cr reduction treatment step were performed by the AOD method. After the Cr reduction treatment step, a slag removal step of removing slag from the molten steel was performed. Then, a known final decarburization refining step and a Cr reduction treatment step were performed by the VOD method.

[0312] After the Cr reduction treatment step by the VOD method, the molten steel in the ladle was subjected to final composition adjustment by LT in the same manner as in Example 1. At this time, the molten steel to which Ca was added after Mg was marked as "A" in the "Mg-Ca addition order" column in Table 5. On the other hand, the molten steel to which Mg was added after Ca was added was marked as "NA" in the "Mg-Ca addition order" column in Table 5.

[0313] In addition, in each test number other than test number 52, the holding time tA (seconds) from the addition of Mg and the lapse of uniform mixing time τ to the addition of Ca was adjusted as shown in Table 5. In each test number other than test number 52, the holding time tB (seconds) from the addition of Ca and the lapse of uniform mixing time τ to the tapping of steel was adjusted as shown in Table 5. In addition, in test number 52, the time from the addition of Ca and the lapse of uniform mixing time τ to the addition of Mg is shown in Table 5 as the holding time tA (seconds). In test number 52, the time from the addition of Mg and the lapse of uniform mixing time τ to the tapping of steel is shown in Table 5 as the holding time tB (seconds). In addition, in each test number, FnC (= tA / tB) calculated from the holding time tA (seconds), the holding time tB (seconds) and the above formula (C) is shown in Table 5. Through the above steps, molten steel with the chemical composition shown in Tables 4-1 and 4-2 was produced.

[0314] In the same manner as in Example 1, steel ingots are manufactured by the ingot casting method from the molten steel of each test number. The steel ingot of each test number is heated at 1250°C for 3 hours. The heated steel ingot is hot forged to manufacture a plurality of blocks for each test number. One block of each test number is hot rolled. Specifically, after the block of each test number after hot forging is heated at 1230°C for 3 hours, hot rolling is performed. Thus, steel materials (steel plates) of each test number having a thickness of 13 mm are manufactured.

[0315] The steel materials of each test number were quenched in the same manner as in Example 1. Specifically, the steel plates of each test number were kept at 910°C for 15 minutes and then water-cooled. The steel plates of each test number after quenching were tempered at the tempering temperature (°C) described in Table 5 for the tempering time (minutes) described in Table 5. The steel plates of each test number were manufactured through the above manufacturing process.

[0316] [Evaluation test]

[0317] The produced steel plates of each test number were subjected to a tensile test, a specific inclusion number measurement test, a hot workability test, and a corrosion resistance test.

[0318] [Tensile test]

[0319] For the steel plates of each test number, tensile tests were performed in accordance with ASTM E8 / E8M (2021). Specifically, a round bar tensile test piece with a diameter of 8.9 mm and a gauge length of 35.6 mm in the parallel portion was made from the central position of the plate thickness of the steel plate of each test number. The length direction of the round bar tensile test piece is parallel to the rolling direction of the steel plate. Using the round bar tensile test piece of each test number, a tensile test was performed in the atmosphere at room temperature (24±3°C) to determine the 0.2% residual deformation stress (MPa). The determined 0.2% residual deformation stress is defined as the yield strength (MPa). The yield strength of each test number obtained is shown in the "YS (MPa)" column of Table 6.

[0320] [Table 6]

[0321] Table 6

[0322]

[0323] [Specific inclusion count measurement test]

[0324] For the steel plates of each test number, the total number density (number / cm2) of Ca oxides (coarse Ca oxides) with a circle equivalent diameter of 2.0 μm or more and Ca sulfides (coarse Ca sulfides) with a circle equivalent diameter of 2.0 μm or more was determined by the above method. 2 ), and the number density (pcs / cm2) of Mg oxides with a circle equivalent diameter of 2.0 μm or more (coarse Mg oxides) 2 The total number density of coarse Ca oxides and coarse Ca sulfides obtained for each test number is shown in "Ca(O,S) (number / cm 2 The number density of coarse Mg oxides obtained for each test number is shown in the "MgO (pieces / cm 2The total number density of coarse Ca oxides, coarse Ca sulfides and coarse Mg oxides for each test number is shown in the "Specific inclusions (individuals / cm 2 In addition, the ratio of the number of coarse Mg oxides to the number of specific inclusions in each test number is shown in the "MgO ratio (%)" column of Table 6.

[0325] [Hot workability test]

[0326] For the blocks of each test number, a hot workability test (Greeble test) was implemented by the above method. In addition, as mentioned above, the blocks of each test number refer to blocks obtained by hot forging the steel ingots manufactured by the molten steel of each test number. Round bar test pieces are made from the blocks of each test number. Specifically, for the blocks of each test number, the direction of hot rolling (equivalent to the rolling direction of the manufactured steel plate) is determined. In addition, the surface of the block of each test number, the surface where hot rolling is implemented (the surface perpendicular to the plate thickness direction of the steel plate) is determined. In the cross section perpendicular to the direction where hot rolling is implemented (rolling direction of the steel plate) of the block of each test number, a round bar test piece is made from the intersection of two diagonals and the center position of the surface where hot rolling is implemented.

[0327] The round bar test piece was 10 mm in diameter and 130 mm in length. The length direction of the round bar test piece was parallel to the direction in which the block was hot rolled (rolling direction of the steel plate). After heating the round bar test piece of each test number to 900°C, the strain rate was 10 s -1 A tensile test was performed to break the round bar test piece of each test number. The neck shrinkage value Ra (%) was determined from the broken round bar test piece of each test number. The obtained neck shrinkage value Ra of each test number is shown in the "Ra (%)" column of Table 6.

[0328] [Corrosion resistance test]

[0329] For the steel plates of each test number, the corrosion resistance test (corrosion rate test) was carried out in the above-mentioned method. Specifically, a test piece with a length of 30 mm, a width of 20 mm, and a thickness of 2 mm was made from the center of the plate thickness of the steel plates of each test number. Among them, the length direction of the test piece is parallel to the rolling direction. The test pieces of each test number were immersed in a 5.0 mass % sodium chloride aqueous solution in an autoclave. In the autoclave, a mixed gas (SO2, NO2 and CO2) with a total pressure of 130 bar, a SO2 concentration of 10 ppm, and a NO2 concentration of 10 ppm was pressurized and sealed. The temperature in the autoclave was maintained at 175°C, and a corrosion rate test was carried out for 96 hours.

[0330] For the test piece after 96 hours, the corrosion rate (mm / year) was calculated from the mass, density and surface area. For the test piece after 96 hours, a magnifying glass with a magnification of 10 times and an optical microscope with a magnification of 100 times were also used to observe the presence or absence of pitting. When the corrosion rate obtained is less than 0.100 mm / year and no pitting is confirmed, it is judged to have better corrosion resistance in a corrosive environment mixed with SOx and NOx ("EX" in the "Corrosion Resistance (175°C)" column in Table 6). On the other hand, when the corrosion rate obtained exceeds 0.100 mm / year or pitting is confirmed, it is judged not to have better corrosion resistance in a corrosive environment mixed with SOx and NOx ("NA" in the "Corrosion Resistance (175°C)" column in Table 6). The evaluation of corrosion resistance of each test number is shown in Table 6.

[0331] [Evaluation results]

[0332] Referring to Table 4-1, Table 4-2, Table 5 and Table 6, the chemical composition of the steel plates of test numbers 28 to 45 is appropriate, and Fn1 is 0.0010 to 0.0050. These steel plates also have a yield strength of 862 MPa or more. In these steel plates, the ratio of the number of coarse Mg oxides to the number of specific inclusions is 45.0% or more. As a result, these steel plates have better corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test. In addition, based on these evaluation results, it is judged that these steel plates have a microstructure composed of 0 to 5% retained austenite, 0 to 5% ferrite, and the balance is martensite by volume.

[0333] The steel sheets of test numbers 28 to 42 also had Fn2 of 0.80 or more, and were manufactured by the above-mentioned preferred manufacturing method. As a result, the total number density of specific inclusions in these steel sheets was 1000 pieces / cm 2 As a result, these steel sheets had neck reduction values ​​Ra of 70% or more in the hot workability test, showing excellent hot workability.

[0334] On the other hand, the Ca content of the steel sheet of Test No. 46 was too low.

[0335] The Fn1 of the steel sheets of test numbers 47 and 48 was too high. As a result, in these steel sheets, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, these steel sheets did not show better corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0336] The Mg content of the steel sheet of test number 49 was too low. As a result, in the steel sheet, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, the steel sheet did not show better corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0337] The steel sheets of test numbers 50 and 51 had too low a Ca content, too low a Mg content, and too low a Fn1.

[0338] In the steel plate of test number 52, Mg was added after Ca was added when the molten steel was produced. As a result, in the steel plate, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, the steel plate did not show better corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0339] The Cu content of the steel sheet of test number 53 was too high.

[0340] The Cr content of the steel sheet of test number 54 was too low. As a result, the steel sheet did not show more excellent corrosion resistance in a corrosive environment mixed with SOx and NOx in a corrosion resistance test.

[0341] The Ni content of the steel sheet of test number 55 was too low.

[0342] The steel sheet of test number 56 had an excessively low Mo content. As a result, the steel sheet did not exhibit more excellent corrosion resistance in a corrosive environment mixed with SOx and NOx in a corrosion resistance test.

[0343] In the steel sheet of test number 57, FnC was too small when molten steel was produced. As a result, in the steel sheet, the ratio of the number of coarse Mg oxides to the number of specific inclusions was less than 45.0%. As a result, the steel sheet did not show better corrosion resistance in a corrosive environment mixed with SOx and NOx in the corrosion resistance test.

[0344] The embodiments of the present disclosure have been described above. However, the above embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments may be appropriately modified within the scope of the present disclosure.

Claims

1. A martensitic stainless steel material, wherein C is 0.030% or less by mass, Si: 1.00% or less, Mn: 1.00% or less, P: 0.030% or less, S: 0.0050% or less, Cr:11.00~14.00%、 Ni: 4.00~7.50%, Mo: 1.50-4.50%, Co: 0.01-0.50%, Ti: 0.05-0.30%, V:0.01~1.00%、 Ca: 0.0005~0.0050%, Mg: 0.0005~0.0050%, Al:0.001~0.100%、 N: 0.0500% or less, O: 0.0500% or less, Cu: 0-3.50%, Nb: 0-0.50%, Zr:0~0.050%、 W:0~2.00%、 B:0~0.0050%、 Rare earth elements: 0 to 0.0050%, and Balance: Fe and impurities, Within the content range of the element of the martensitic stainless steel material, the content of the element satisfies the formula (1), The yield strength of the martensitic stainless steel is 862 MPa or more. In the martensitic stainless steel, The number ratio of Mg oxides having a circle equivalent diameter of 2.0 μm or more to Ca oxides having a circle equivalent diameter of 2.0 μm or more, Ca sulfides having a circle equivalent diameter of 2.0 μm or more, and Mg oxides having a circle equivalent diameter of 2.0 μm or more is 45.0% or more, 0.0010≤Ca+Mg≤0.0050 (1) Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (1).

2. The martensitic stainless steel material according to claim 1, wherein: It contains a selection of Cu: 0.01~3.50%, Nb: 0.01-0.50%, Zr:0.001~0.050%、 W:0.01~2.00%、 B: 0.0001~0.0050%, and Rare earth elements: one or more elements selected from the group consisting of 0.0001 to 0.0050%.

3. The martensitic stainless steel material according to claim 1 or 2, wherein: Within the content range of the element of the martensitic stainless steel material, the content of the element satisfies the formula (2), In the martensitic stainless steel, The total number density of the Ca oxide with a circle equivalent diameter of 2.0 μm or more, the Ca sulfide with a circle equivalent diameter of 2.0 μm or more, and the Mg oxide with a circle equivalent diameter of 2.0 μm or more is 1000 / cm 2 above, Ca / S≥0.80 (2) Here, the content of the corresponding element is substituted in mass % at the element symbol in formula (2).